2021
DOI: 10.1016/j.scitotenv.2020.142742
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term irrigation with municipal reclaimed wastewater on the uptake and degradation of organic contaminants in lettuce and leek

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…For a concentration of 5 µg L −1 , renal lesions were evident, as well as drug bioaccumulation in the liver, kidneys, gills and muscles [ 5 , 6 ]. The occurrence of DCF in different aquatic compartments and effluents of wastewater, surface water and groundwater is detected in a wide low-concentration range from 0.8 ng L −1 up to 4.4 mg L −1 [ 7 , 8 ], which highlighted that the mentioned negative effects are of sufficient magnitude to suspect chronic toxicity in aquatic organisms. Based on such facts, the removal of non-biodegradable, biologically active micropollutants from wastewaters is important to minimize their potential negative effect on all living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…For a concentration of 5 µg L −1 , renal lesions were evident, as well as drug bioaccumulation in the liver, kidneys, gills and muscles [ 5 , 6 ]. The occurrence of DCF in different aquatic compartments and effluents of wastewater, surface water and groundwater is detected in a wide low-concentration range from 0.8 ng L −1 up to 4.4 mg L −1 [ 7 , 8 ], which highlighted that the mentioned negative effects are of sufficient magnitude to suspect chronic toxicity in aquatic organisms. Based on such facts, the removal of non-biodegradable, biologically active micropollutants from wastewaters is important to minimize their potential negative effect on all living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Manasfi et al [46] used the QuEChERS method to extract diclofenac, metoprolol, clarithromycin, climbazole and carbamazepine from soils after irrigation with treated wastewater spiked with 10 µg L −1 of each contaminant. These authors found concentration levels in soil in the 1-30 ng g −1 (d.w.) range, however they did not report results in terms of recoveries and validation of the extraction method.…”
Section: Lc-hrms Determination Of Pharmaceuticals Residuesmentioning
confidence: 99%
“…Each reactor was filled with 4 L of treated wastewater, and water level was kept constant by means of constant water addition using a peristaltic pump ensuring a hydraulic retention time equal to 24 h and no external nutrients were supplied for biofilm growth. Treated wastewater was collected from the wastewater treatment plant operated on the basis of stabilization ponds with three successive lagoons (13,680, 4784 and 2700 m 3 , respectively), without addition of disinfection processes and had a nominal capacity of 1500 Inhabitant Equivalent (Manasfi et al 2021). The reactors were operated in dark in order to reproduce the irrigation pipe conditions in anaerobic conditions (O2< 0.1 mg L -1 ) by continuously feeding with treated wastewater stored in 200 L tanks in the laboratory (T = 20 ± 2 °C).…”
Section: Biofilm Growth Conditionsmentioning
confidence: 99%